Common Pediatric Hand Anomalies - McCarter, Jacob H.; Zeledon, Ricardo A.; Cole, Samuel H.; Layon, Sarah A.; Nguyen, Jenny Lee (Seminars in Plastic Surgery, 2023)
Upper extremity congenital anomalies in the newborn are second only to congenital heart anomalies. Some of the more commonly encountered upper extremity anomalies are trigger thumb, thumb hypoplasia, polydactyly, syndactyly, and amniotic band syndrome. While some conditions occur in isolation, others are known to commonly occur in association with syndromes. Familiarity with these conditions is important not only to provide adequate evaluation and workup of these patients but also to deliver appropriate surgical intervention and prepare parents with appropriate expectations. In this article, we outline the etiology, classification, surgical management, and outcomes of these five commonly encountered upper extremity congenital anomalies.
Keywords: upper extremity; congenital hand; thumb hypoplasia; syndactyly; trigger thumb; amniotic band syndrome; polydactyly